Generalized KdV and Burger Equations and Various Vanishing Limits - Shrestha, Pawan; KC, Durga Jang; Sharma, Ramjee (Journal of Institute of Science and Technology, 2023)
In this analytical and numerical study, we look at the generalized KdV equation by letting different coefficients go to zero. Numerical study is carried out by the pseudospectral method. Our study shows that there is no difference between the behavior of the solutions in the limiting case and the solutions in the case when the corresponding coefficients are exactly zero.